The Panza di Biumo Donation To the Museo Cantonale d'Arte : Sguardi sulla Collezione dello Stato del Cantone Ticino. - Disch, Maddalena; Franciolli, Marco; Kahn-Rossi, Manuela (Lugano : Museo Cantonale d'Arte, 1997)
Ackling, Roger ; Arends, Stuart ; Ball, Barry X ; Beckman, Ford ; Carroll, Lawrence ; Fredenthal, Ruth Ann ; Graham, Allan ; Graham, Gloria ; Griffin, Ron ; Horn, Roni ; Hyde, James ; Kiecol, Hubert ; Klingelhöller, Harald ; Lere, Mark ; Levine, Daniel ; Mahoney, Gregory ; Roeth, Winston ; Rudel, Ross ; Saxon, Erik ; Schütte, Thomas ; Schorovski, Carole ; Shelton, Peter ; Simpson, David ; Spalletti, Ettore ; Therrien, Robert ; Thurston, Roy ; Tiemann, Robert ; Vercruysse, Jan ; Webster, Meg
biografie, bibliografie
Engels
boek